Early results from implementation of a 'watch and wait' protocol for complete clinical response following chemoradiotherapy for rectal cancer. Issue 11 (15th July 2022) - Balasuriya, Hasitha D.; Timon, Charles; Entriken, Fiona; Neely, David; Herron, John; Tang, Colin; Van Hazel, Guy; Warner, Michael W.
Abstract: Background: Neoadjuvant long course chemoradiotherapy (NLCRT) for rectal cancer can result in complete pathological response (pCR). In 2017, we started offering patients who had a complete clinical response (cCR), a choice between total mesorectal excision (TME) and an intensive surveillance or 'watch and wait' (W&W) program. We report the early outcomes of this prospective study. Methods: All patients undergoing NLCRT from 2017 to 2019 were included. All patients were restaged at 8 weeks, and those who had a cCR were offered TME or W&W. Results: Of 59 patients who underwent NLCRT, 55 had restaging. Eleven of these patients had a cCR (20%). Three chose to have TME and all had a pCR. Eight were enrolled in W&W. Two patients were diagnosed with local regrowth and underwent TME at 7 and 17 months after NLCRT. A further nine patients, who were surgically unfit or refused TME, and had an excellent response to NLCRT, but one that did not reach criteria for a cCR, were also managed with W&W. Of these, two patients developed regrowth with distant metastases. From 2017 to 2019, of the 17 patients who were managed with a W&W approach, 13 patients have remained regrowth free after a median of 28 (13–58) months of W&W. Conclusion: Preliminary findings suggest management with W&W, following cCR, may be a safe alternative to TME. There have so far been no instances of distant failure, and those with cCR that had regrowth, were identified early and successfully managed with salvage TME. Abstract : Organ preservation following a complete clinical response of rectal cancer to neoadjuvant long course chemoradiotherapy is gaining traction worldwide, however is not yet standard of care in Australia. This article describes an Australian experience of a watch‐and‐wait approach and the early results, since its implementation in 2017.